The potential of implementing Building Information Modelling (BIM) in Malaysian Construction Industry: An exploratory study - Zahrizan, Zakaria; Nasly, Mohamed Ali; Amanda, Marshall-Ponting; Ahmad Tarmizi, Haron; Zuhairi, Abd. Hamid (Universiti Malaysia Pahang, 2012)
In Malaysia, we cannot deny the widespread of Information and Communication Technology (ICT) and the influence of ICT to speed up the working process. Lots of benefits can be gained from utilisation of ICT, especially in construction industry. For decade, construction industry can be considered as a fragmented industry because of lacking of sharing information through its life cycle and with other parties. ICT can be a tool for integrating and collaborating among parties in the construction projects, and Building Information Modelling (BIM) is one of the platforms that can be used to promote the collaboration between parties in the construction projects. Eastman et al., 2011, interpreted BIM as “a digital representation of the building process to aid in exchanging and interoperability information in a digital format." Basically, BIM will act like a respiratory system with full of information to share with for construction projects. Even though there are lots of benefits can be gained by utilisation of BIM, it is a difficult task to convince the construction companies to embrace and implementing it due to some reasons. Since there is a short of understanding of BIM by the construction companies in Malaysia, this paper is intended to review the strategy and action plan from Singapore and Hong Kong in adopting and implement BIM, which could be used in supporting the implementation of BIM in Malaysian Construction Industry. As a summary, this paper revealed that involvement from government, collaboration between government, private sector and universities and awareness program are the most of the important criteria that must be taken into consideration once to developing BIM implementation strategy plan for Malaysian construction industry.